Investigation into the mechanism underlying the antiproliferative and apoptotic effects of pyrrolo-1,5-benzoxazepine compounds - Mulligan, Jude (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2004)
A novel series of pyrrolo-1,5-benzoxazepine (PBOX) compounds have potential as anti-cancer agents. The PBOX compounds appear to be subdivided into two groups, those that exert antiproliferative effects (e.g. PBOX-21) by arresting cancerous cells in the G1 phase of the cell cycle without eliciting cytotoxic effects, and those that induce apoptotic cell death (e.g. PBOX-6 ). A fuller understanding of the molecular mechanisms underlying the oncostatic and apoptotic effects of these PBOX compounds is essential to their development as therapeutic agents in the treatment of cancer.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin